Cardiorespiratory Fitness and the Risk of First Acute Myocardial Infarction: The HUNT Study - Shigdel, Rajesh (J Am Heart Assoc, 2019)
BACKGROUND: The majority of studies evaluating cardiorespiratory fitness (CRF) as a cardiovascular risk factor use cardiovascular mortality and not cardiovascular disease events as the primary end point, and generally do not include women. The aim of this study was to investigate the association of estimated CRF (eCRF) with the risk of first acute myocardial infarction (AMI). METHODS AND RESULTS: We included 26 163 participants (51.5% women) from the HUNT study (Nord‐Trøndelag Health Study), with a mean age of 55.7 years, without cardiovascular disease at baseline. Baseline eCRF was grouped into tertiles. AMI was derived from hospital records and deaths from the Norwegian Cause of Death Registry. We used Fine and Gray regression modeling to estimate subdistribution hazards ratio (SHR) of AMI, accounting for competing risk of death. During a mean (range) follow‐up of 13 (0.02–15.40) years (347 462 person‐years), 1566 AMI events were recorded. In fully adjusted models men in the 2 highest eCRF had 4% (SHR: 0.96, 95% CI: 0.83–1.11) and 10% (SHR: 0.90, 95% CI: 0.77–1.05) lower SHR of AMI, respectively, when compared with men in the lowest tertile. The corresponding numbers in women were 12% (SHR: 0.88, 95% CI: 0.72–1.08) and 25% (SHR: 0.75, 95% CI: 0.60–0.95). CONCLUSIONS: eCRF was inversely associated with risk of AMI event among women but not in men. Our data suggest that high eCRF may have substantial benefit in reducing the risk of AMI. Therefore, our data suggest that an increased focus on eCRF as a cardiovascular disease risk marker in middle‐aged and older adults is warranted.